Endoscopic Techniques for Lumbar Interbody Fusion: Principles and Context. (19th March 2022) - Zheng, Bryan; Shaaya, Elias; Feler, Josh; Leary, Owen P.; Hagan, Matthew J.; Bajaj, Ankush; Fridley, Jared S.; Hassel, Frank; Gardocki, Raymond; Grau, Ricardo Casal; Lewandrowski, Kai-Uwe; Telfeian, Albert E.
Abstract : Endoscopic techniques in spine surgery are rapidly evolving, with operations becoming progressively safer and less invasive. Lumbar interbody fusion (LIF) procedures comprise many spine procedures that have benefited from endoscopic assistance and minimally invasive approaches. Though considerable variation exists within endoscopic LIF, similar principles and techniques are common to all types. Nonetheless, innovations continually emerge, requiring trainees and experienced surgeons to maintain familiarity with the domain and its possibilities. We present two illustrative cases of endoscopic transforaminal lumbar interbody fusion with a comprehensive literature review of the different approaches to endoscopic LIF procedures.